Dynamic Crack Propagation Problems of Fibre-Reinforced Concrete. (8th March 2012) - Cheng, Y. H.; Chun, Lu Nian; Xin-gang, Li
Abstract : Applying the built dynamic crack model of fibre concrete, bridging fiber segment is substituted by loads. When a crack propagates its fiber continues to break. By the approaches of the theory of complex functions, the problems dealt with can be translated into Riemann-Hilbert problems. Analytical solutions of the displacements, stresses, and dynamic stress intensity factors under the action of of moving variable loads P x 2 / t 2 and P t 3 / x 2, respectively, are attained by the ways of self-similar measures. After those analytical solutions are utilized by superposition theorem, the solutions of arbitrary complex problems can be obtained.